Apostle Paul’s Vocation as the Turning Point of Religious Education from Monocultural to Multicultural - Agus Marulitua Marpaung; Byung June Hwang (Sekolah Tinggi Teologi Intheos Surakarta, 2023)
Christians in this globalization era live in multicultural society. Therefore, multicultural education requires attention. Apostle Paul's vocation is an important moment about the turning point from monocultural to multicultural ministry. God's commission for the Twelve Apostles to teach and baptize to the ends of the earth, was apparently not fully understood by the Twelve Apostles. They are still Israel-centered minded in mission. By using literature study method, this article aimed to analyze the theological meaning of Paul's vocation in relation to religious education in multicultural context. The result of this study showed that the teaching and life of Apostle Paul had given some insight to accomplish religious education in multicultural context, by implementing contextual religious education. Therefore it could be concluded that religious education must always be aware of the students' life context. Awareness of this context includes awareness of their needs and potention.